2011
DOI: 10.3928/01477447-20111021-11
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Lipomatous Tumors/Well-differentiated Liposarcomas: Clinical Outcome of 67 Patients

Abstract: Atypical lipomatous tumors/well-differentiated liposarcomas are low-grade malignant mesenchymal neoplasms with high propensity to local recurrence and potential to dedifferentiate to higher grades over time. However, the published risks of local recurrence and dedifferentiation vary, and no unified treatment and follow-up plan has been accepted. We performed a study to evaluate the long-term clinical behavior and proper treatment and follow-up strategy for these tumors. We retrospectively reviewed the files of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
46
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 27 publications
8
46
1
Order By: Relevance
“…In contrast to the prior study by Jelinek et al, 15 in which 11 of 12 cases of ALT were unencapsulated, all cases of ALT in our study (10/10) contained a tumor capsule radiologically. In keeping with multiple prior case series, 16,17 we saw no metastases in patients with ALT.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast to the prior study by Jelinek et al, 15 in which 11 of 12 cases of ALT were unencapsulated, all cases of ALT in our study (10/10) contained a tumor capsule radiologically. In keeping with multiple prior case series, 16,17 we saw no metastases in patients with ALT.…”
Section: Discussionsupporting
confidence: 90%
“…In past literatures, these recurrences have been reported to be between 40 and 67%. 3,5,6,9,13,18 In this current study, 2 out of 3 cases (67%) that underwent reoperation after recurrence demonstrated multiple recurrences, both of which were operated with marginal resection. Thus, preference for reoperation for recurrence is given to wide resection; however, because reoperation often reveals strong adhesion and makes contact with important nerves and vessels, the demerits of wide resection should also be considered.…”
Section: Discussionmentioning
confidence: 48%
“…Those who recommend marginal resections have suggested the limitations of their research in terms of their short follow-up periods, and also note that recurrence rates can increase as the follow-up period is increased in duration. 8,9 Rozental et al 6 and Macrogenesis et al 18 both report the necessity of at least 5 or 6 years follow-up, and we set the general median-term follow-up of 5 or more years as a cutoff point of our observation period. Among studies describing the clinical outcome of ALT in the extremities, our study has the longest minimum follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies report complete excision of well-differentiated liposarcomas and atypical lipomatous tumors due to high risk of local recurrence. [10] Higher-grade liposarcoma in the retroperitoneum, where wide surgical excision is difficult to achieve, may receive adjuvant radiation therapy. All subtypes of liposarcoma will benefit from complete resection to minimize recurrence.…”
Section: Discussionmentioning
confidence: 99%